Analysis of Chemical Constituents of Traditional Chinese Medicinal Formula Huang-Qi-Chi-Feng-Tang by High Performance Liquid Chromatography-Electrospray Ionization-Mass Spectrometry - Xu, Jingjing; Zhu, Yingchao; Lin, Li; Jiang, Yanyan; Liu, Bin (Asian Journal of Chemistry, 2013)
Huang-Qi-Chi-Feng-Tang, a three-herb traditional Chinese medicinal formula, has efficient effects on treatment of skin ulcer and pains. However, the active components of this compound Chinese prescription have not been fully explored. In this study, high performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) was applied for the qualitative analysis of major chemical constituents in Huang-Qi-Chi-Feng-Tang. Samples were separated on a Waters Symmetry Shield C18 column (150 mm × 4.6 mm) using a gradient system of 20 % methyl alcohol (A)-methyl alcohol (B). The precursor and product ions of analytes were monitored on a hybrid quadrupole linear ion trap mass spectrometer in negative mode. A total of 11 compounds including 3 chromones, 2 monoterpenoids, 5 isoflavone, 1 isoflavane were successfully identified or tentatively characterized based on retention time and MS spectra compared with those of standards or literature data. The results may contribute to the new drug development and illuminate the effective substance basis.